2018
DOI: 10.1029/2018wr023306
|View full text |Cite
|
Sign up to set email alerts
|

Household Water Use and Conservation Behavior: A Meta‐Analysis

Abstract: Understanding the psychological‐social drivers of water‐use behavior in households is essential for enhancing the effectiveness of water‐conservation strategies and subsequent environmental benefits. This study used the Behaviour Change Wheel framework to review associations between capability, opportunity, and motivation (COM) dimensions and household water‐use behaviors. A meta‐analysis of 88 correlation coefficients from a combined sample of 15,656 participants showed positive relationships between water‐us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 84 publications
(84 reference statements)
1
20
0
Order By: Relevance
“…The BCW framework and COM-B system have been applied in several disciplines and contexts (e.g. Addo et al 2018;Alexander et al 2014;Barker et al 2016;Jackson et al 2014;McLeod et al 2015). Addo et al (2018) found that the psychological-social factors of capability, opportunity, and motivation are the mechanisms of changing behaviour in water conservation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BCW framework and COM-B system have been applied in several disciplines and contexts (e.g. Addo et al 2018;Alexander et al 2014;Barker et al 2016;Jackson et al 2014;McLeod et al 2015). Addo et al (2018) found that the psychological-social factors of capability, opportunity, and motivation are the mechanisms of changing behaviour in water conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Addo et al 2018;Alexander et al 2014;Barker et al 2016;Jackson et al 2014;McLeod et al 2015). Addo et al (2018) found that the psychological-social factors of capability, opportunity, and motivation are the mechanisms of changing behaviour in water conservation. The authors contended that these mechanisms determine specific intervention strategies to target more effective measures and solutions that promote sustainable water-conservation behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The COM-B model links to a framework of interventions and policies, the Behaviour Change Wheel, which in turn links to a taxonomy of 93 specific behaviour change techniques (Michie et al, 2011(Michie et al, , 2013. These tools can be used to inform the development and evaluation of interventions and policies concerning behaviour change, including increasing health and sustainability following COVID-19 restrictions (Michie et al, 2020) and reviewing pro-environmental behaviour change interventions (Addo et al, 2018;Hedin et al, 2019;Staddon et al, 2016). Behaviour change theory can be used to hypothesise influences on identified behaviour changes that occurred during periods of COVID-19 related restrictions and guidance and to suggest ways to maintain behaviour changes likely to promote climate mitigation (Bouman et al, 2020).…”
Section: Insights From Behavioural Science Relating To Covid-19 Related Behaviour Change and Potential Impact On Climate Changementioning
confidence: 99%
“…One critique of the TPB for predicting natural resource conservation is that it only encompasses basic variable-effect relationships [23]. However, extended models of the TPB have been used successfully with natural resource conservation behaviors [32] and the importance of investigating additional moderating effects for the framework are acknowledged in the literature [39].…”
Section: Introductionmentioning
confidence: 99%